Interactive effects of high n-3 PUFA intake and cyclic heat stress under two dietary antioxidant levels in broiler chickens - Rezar, Vida; Pal, Manca Pečjak; Levart, Alenka; Nemec Svete, Alenka; Pirman, Tatjana; Salobir, Janez; Leskovec, Jakob (Frontiers in Physiology, 2025)
The study examined the combined effects of a diet high in n-3 PUFAs and cyclic heat stress (HS) considering two levels of dietary antioxidants. A total of 192 one-day-old male Ross 308 broilers were divided into eight groups in a 2 × 2 × 2 factorial design: thermoneutral (TN) or heat-stressed (34°C ± 1°C for 7 h/day from day 22) × fed a diet low in antioxidants (NRC group) or high in antioxidants (HAOX group; supplemented with a mixture of 200 IU/kg vitamin E, 250 mg/kg vitamin C and 0.15 mg/kg selenium) and supplemented or not with 5% linseed oil, forming the NRC N-3 and HAOX N-3 groups. High intake of n-3 PUFAs increased plasma F2-isoprostane and malondialdehyde (MDA) levels and superoxide dismutase (SOD) activity. Cyclic HS decreased final body weight (BW) and average daily feed intake (ADFI) and increased DNA damage and serum corticosterone (CORT) levels. In addition, the changes in blood biochemistry indicated that the broilers were undergoing respiratory alkalosis. Interactions between n-3 PUFAs and HS were observed in liver MDA levels, plasma γ-tocopherol levels and serum alkaline phosphatase (AP) activity. Antioxidants increased blood levels of α-tocopherol, vitamin C, lipid- and water-soluble antioxidants and glutathione peroxidase (GPx) activity, while decreasing MDA, F2-isoprostane, CORT and AP levels. High intake of n-3 PUFA in combination with cyclic HS had negative effects on the health status of the broilers, which were alleviated by additional antioxidant supplementation.